Demands for Modern Shipping and SUiveillance of the Adriatic Sea - Lakota, Martin (Promet - Traffic&Transportation, 2006)
In this work modem navigation and Adriatic control demandcharacteristics are developed. It correlates the modemnavigation characteristics and the Adriatic sea control. Thepresent operating procedures used for sea control are mentionedas well as the new systems and procedures based on newcomputer and communication technologies (automatic identificationsystems, GPS, computer networks, Internet/Intranetstandards). It discusses unmanned aerial vehicles characteristicsaccording to demands and grading standards for picture/scene interpretation (NIIRS grading scale).